The Effect of Media Exposure on Customer Loyalty Through Brand Image among Users of Sicepat Ekspress Shipping Services - Setiawan, Ariq Rifqi; Rahmi, Palupi Permata; Mubarok, Dadan Abdul Aziz (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the influence of media exposure on customer loyalty and analyzes the role of customer loyalty in shaping brand image in the courier service industry, focusing on users of SiCepat Ekspres in Indonesia. The rapid growth of e-commerce has intensified competition among logistics providers, making digital media exposure and customer experience increasingly important in maintaining customer relationships and brand perception. This research adopts a quantitative survey approach by collecting data from 100 respondents who had used SiCepat Ekspres services and were exposed to related information on digital media platforms. Respondents were selected using purposive sampling based on service usage and media exposure criteria. The data were analyzed using path analysis to examine the relationships among media exposure, customer loyalty, and brand image. The findings show that media exposure has a significant positive effect on customer loyalty, indicating that repeated exposure to brand-related information strengthens customer attachment and intention to reuse the service. However, media exposure does not have a significant direct effect on brand image. Customer loyalty, on the other hand, has a strong and significant influence on brand image, suggesting that brand perception in courier services is primarily shaped by accumulated service experience rather than media communication alone. This study contributes to the literature by repositioning customer loyalty as a key mechanism in the formation of brand image. Practically, the findings suggest that courier service providers should prioritize service reliability and customer experience while using media exposure strategically to reinforce customer loyalty.